Stefan BERGER, History and Identity: How Historical Theory Shapes Historical Practice, Cambridge 2022, Cambridge University Press, 493 s., ISBN 978-1-107-64884-5 - Šuch, Juraj (Dějiny – teorie – kritika, 2025)
Book review